Multi-Hit action of membrane active peptides: towards understanding bacterial cell killing - Moiset, Gemma; Cirac, Anna D.; Mika, Jacek T.; Kocer, Armagan; Stuart, Marc C. A.; Sengupta, Durba; Marrink, Siewert-Jan; Poolman, Bert (Biophysical Journal, 2012)
56th Annual Meeting of the Biophysical-Society, San Diego, CA, FEB 25-29, 2012

Dual action of BPC194: a membrane active peptide killing bacterial cells - Moiset, Gemma; Cirac, Anna D.; Stuart, Marc C. A.; Marrink, Siewert-Jan; Sengupta, Durba; Poolman, Bert (Plos One, 2013)
Membrane active peptides can perturb the lipid bilayer in several ways, such as poration and fusion of the target cell membrane, and thereby efficiently kill bacterial cells. We probe here the mechanistic basis of membrane poration and fusion caused by membrane-active, antimicrobial peptides. We show that the cyclic antimicrobial peptide, BPC194, inhibits growth of Gram-negative bacteria and ruptures the outer and inner membrane at the onset of killing, suggesting that not just poration is taking place at the cell envelope. To simplify the system and to better understand the mechanism of action, we performed Forster resonance energy transfer and cryogenic transmission electron microscopy studies in model membranes and show that the BPC194 causes fusion of vesicles. The fusogenic action is accompanied by leakage as probed by dual-color fluorescence burst analysis at a single liposome level. Atomistic molecular dynamics simulations reveal how the peptides are able to simultaneously perturb the membrane towards porated and fused states. We show that the cyclic antimicrobial peptides trigger both fusion and pore formation and that such large membrane perturbations have a similar mechanistic basis.